Respon Pemberian Pupuk Kotoran Ayam dan Pupuk Organik Cair terhadap Produksi Tanaman Kedelai - Luta, Devi Andriani; Br. Sitepu, Sri Mahareni (JURNAL AGROPLASMA, 2025)
Obtaining soybeans with good yields can utilize chicken manure fertilizer and liquid organic fertilizer from water hyacinth. This study aims to determine the effectiveness of chicken manure fertilizer and liquid organic fertilizer from water hyacinth on soybean plant production. The research method used a Factorial Randomized Block Design (RBD) consisting of 2 factors with 16 treatment combinations and 2 blocks. The factors studied were chicken manure fertilizer treatment (A) consisting of 4 levels: 0, 2, 3, and 3 kg/plot. The liquid organic fertilizer from water hyacinth (E) consisted of 4 levels: 0, 300, 400, and 500 ml/liter of water per plot. The parameters observed were: number of pods per plot (pods), pod weight per sample (g), and weight of 100 dry seeds (g). The research results indicate that the effectiveness of chicken manure fertilizer on soybean plant production has a very significant effect on the number of pods per plot (pods), pod weight per sample (g), and 100 dry seed weight (g). The best treatment was the application of chicken manure fertilizer at 3 kg/plot. Keywords: influential, production, treatment